Immigration and School Choice in Australia - Mavisakalyan, Astghik (Blackwell Publishing Asia, 2012)
This article examines the relationship between the share of immigrants in a locality and private versus public school choices of natives and immigrants in Australia. Using the 2001 Australian Census data, it finds that private school attendance among native-born Australians is higher in localities with a higher share of immigrant populations. Immigrants’ private school attendance is lower where the share of their like-type immigrants is higher. These effects vary with the presence of a common language and ethnic background between the natives and the immigrants. Overall, the results suggest the possibility of a ‘flight’ from unfamiliar cultures in the Australian school system.